Os elementos políticos da função normativa das agências reguladoras federais - Ferreira Segundo, Luiz Paulo (2024)
This work aims to analyze the exercise of political power by the federal regulatory agencies in Brazil, especially regarding their normative function. Based on a concept of political power as the ability to determine the public interest goals and the means to achieve them, the work seeks to demonstrate that the federal regulatory agencies make political decisions when they define the objectives of the sectoral policies and the regulatory instruments to implement them. These political decisions, which involve value choices, are not confused with the mere technical application of the law or with the traditional administrative discretion. Therefore, the work argues that these political decisions should be politically controlled by the bodies constitutionally vested with political competence, such as the President of the Republic and the National Congress. To this end, the work analyzes the theoretical arguments and the institutional practices related to the normative function of the federal regulatory agencies, as well as the legal instruments available for the political control of this performance